Estrogen-Dependent Upregulation of Adcyap1r1 Expression in Nucleus Accumbens Is Associated With Genetic Predisposition of Sex-Specific QTL for Alcohol Consumption on Rat Chromosome 4 - Spence, John Paul; Reiter, Jill L.; Qiu, Bin; Gu, Hao; Garcia, Dawn K.; Zhang, Lingling; Graves, Tamara; Williams, Kent E.; Bice, Paula J.; Zou, Yi; Lai, Zhao; Yong, Weidong; et al. (Frontiers in Genetics, 2018)
Humans show sex differences related to alcohol use disorders. Animal model research has the potential to provide important insight into how sex differences affect alcohol consumption, particularly because female animals frequently drink more than males. In previous work, inbred strains of the selectively-bred alcohol-preferring (P) and nonpreferring (NP) rat lines revealed a highly significant quantitative trait locus (QTL) on rat chromosome 4, with a logarithm of the odds score of 9.2 for alcohol consumption. Recently, interval-specific congenic strains (ISCS) were developed by backcrossing the congenic P.NP line to inbred P (iP) rats to further refine the chromosome 4 QTL region. Two ISCS sub-strains, ISCS-A and ISCS-B, were obtained with a narrowed QTL, where the smallest region of overlap consisted of 8.9 Mb in ISCS-B. Interestingly, we found that females from both ISCS lines consumed significantly less alcohol than female iP controls (p < 0.05), while no differences in alcohol consumption were observed between male ISCS and iP controls. RNA-sequencing was performed on the nucleus accumbens of alcohol-naïve female ISCS-B and iP rats, which revealed differentially expressed genes (DEG) with greater than 2-fold change and that were functionally relevant to behavior. These DEGs included down-regulation of Oxt, Asb4, Gabre, Gabrq, Chat, Slc5a7, Slc18a8, Slc10a4, and Ngfr, and up-regulation of Ttr, Msln, Mpzl2, Wnt6, Slc17a7, Aldh1a2, and Gstm2. Pathway analysis identified significant alterations in gene networks controlling nervous system development and function, as well as cell signaling and G-protein coupled receptor signaling. In addition, β-estradiol was identified as the most significant upstream regulator. The expression levels of estrogen-responsive genes that mapped to the QTL interval and have been previously associated with alcohol consumption were measured using RT-qPCR. We found that expression of the Adcyap1r1 gene, encoding the pituitary adenylate cyclase-activating polypeptide type 1 (PAC1) receptor, was upregulated in female ISCS-B compared to female iP controls, while no differences were exhibited in males. In addition, sequence variants in the Adcyap1r1 promoter region showed a differential response to estrogen stimulation in vitro. These findings demonstrate that rat chromosome 4 QTL contains genetic variants that respond to estrogen and are associated with female alcohol consumption.